X-ray photoelectron spectroscopy analysis as a tool to assess factors influencing magnetic anisotropy type in Co/MgO system with gold interlayer. (1st March 2018) - Demchenko, Iraida N.; Syryanyy, Yevgen; Melikhov, Yevgen; Nittler, Laurent; Gladczuk, Leszek; Lasek, Kinga; Cozzarini, Luca; Dalmiglio, Matteo; Goldoni, Andrea; Konstantynov, Pavlo; Chernyshova, Maryna
Abstract: X-ray photoelectron spectroscopy (XPS) studies of Au/Co/Au(0.3 nm)/MgO and Au/Co/MgO systems were conducted in order to monitor the electronic structure modification at Co/MgO interface with/without gold interlayer. A detailed analysis of Co 2 p states revealed that the amount of minor oxygen contribution at Co/MgO interface decreased after the Au interlayer was added. The obtained XPS results together with density functional theory (DFT) allowed explanation of the increase of surface anisotropy energy in the sample with the gold interlayer in terms of (i) noble and transitional metal d - d orbital hybridization; (ii) interfacial Co 3 d and O 2 p ; and (iii) interface imperfection. Graphical abstract: